DISTRIBUSI SPASIAL DAN TEMPORAL JENIS IKAN AIR TAWAR YANG TERTANGKAP DI DANAU IE SAYANG, WOYLA BARAT, ACEH BARAT. - Rika Astuti; Hayatun Nufus; Alaudin MT (Journal of Aceh Aquatic Sciences, 2020)
Research on the distribution of freshwater fish in Lake Ie Sayang, West Woyla is still limited. whereas these fish species are generally of economic value and are ecologically also very important in the balance of freshwater habitats. The purpose of this study was to determine the catch of freshwater fish caught using fishing nets and spatial and temporal distribution patterns of freshwater fish communities in Ie Sayang lake. The study was conducted from June to August 2019 with the direct survey method of spaciousness by catching fish at each fish sampling station in the lake ie Sayang. Determination of the station based on the area of the flow of water in and out of the lake. The number of fish obtained is counted and identified to species level. There were 30 fish found during the study. The highest fish catch in August was 11 fish, and the lowest fish catch in June was 9 fish. Based on the spatial distribution of freshwater fish found in station I and station II, while station III is less than station I and II. The highest temporal distribution of fish was found in August. This is allegedly due to the influence of water temperature. In August it has entered the rainy season in the Ie Sayang lake area. Based on the measurement of water quality, this study shows that the capture of fish is in line with the suitability of water temperature and complexity of the habitats available in Ie Sayang lake.